Highly water-permeable base fabric, artificial turf including same, and manufacturing method
The high-permeable base cloth with specific thread configurations and adhesive composition addresses permeability and durability issues in artificial turfs, ensuring effective water flow and adhesive layer stability.
Patent Information
- Application Number
- JP2023574298
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-12-24
- Filing Date
- 2023-06-25
- Publication Date
- 2025-02-04
- Estimated Expiration
- 2043-06-25
AI Technical Summary
Existing artificial turfs face issues with permeability, leading to weed growth through perforations and quartz sand leakage, which compromises the durability of the adhesive layer.
A high-permeable base cloth is designed with alternating warp and weft threads of specific thickness and density, combined with a specialized adhesive composition to enhance water permeability without perforations, preventing weed growth and sand leakage.
The solution ensures excellent water permeability, maintains adhesive layer integrity, and improves durability by preventing perforations and sand leakage, thus enhancing the overall performance of artificial turfs.
Smart Images

Figure 2025503354000001 
Figure 2025503354000002 
Figure 2025503354000003
Abstract
Description
[Technical field]
[0001] The present invention relates to the field of artificial turf technology, and more particularly to a highly water-permeable base fabric, a method for producing a highly water-permeable base fabric, and an artificial turf including the same and a method for producing the same. [Background technology]
[0002] In April 1966, artificial turf was first used in the world at the Astrodome in Houston, USA, and since then, artificial turf has fully appeared on the world stage. With the development of artificial turf manufacturing technology, it is approaching natural turf in terms of appearance and feel, but it is easier to pave and maintain than natural turf, has lower maintenance costs, and is less affected by the environment, weather, and region. As the application scenarios of artificial turf continue to expand, it is increasingly accepted by people and is increasingly paved in places such as soccer fields, gardens, rooftops, and office buildings. Artificial turf is mainly composed of three parts: synthetic pile fibers that mimic grass blades, a base fabric for planting the synthetic fibers, and a bottom adhesive layer that acts as a fixation. In the process of use, artificial turf is not only noted for its appearance and mechanical performance of the bottom, but also for its water permeability.
[0003] In order to solve the water permeability problem, current artificial turf products adopt the electric trowel drilling method after the adhesive bottom coating process to ensure the water permeability of the product, but during the long-term use of the artificial turf, natural weeds will grow through the holes made by the electric trowel, which makes the subsequent care troublesome. In addition, for some artificial turf, when paving the site, there is a sand filling process, and the quartz sand will leak through the holes to the bottom of the turf and contact the bottom adhesive layer, and the turf will accelerate the wear of the bottom adhesive layer due to the presence of quartz sand during long-term use, and the bottom adhesive layer is prone to fall off over a long period of time, and the turf cannot be covered sufficiently, ultimately resulting in the fall off of the pile.
[0004] Therefore, it is necessary to develop an artificial turf that has excellent water permeability without drilling holes and improves the durability of the bottom surface to meet market needs. Summary of the Invention
[0005] The present invention discloses a highly water-permeable base fabric having excellent water permeability and capable of meeting the requirements of use, and a highly water-permeable and durable artificial turf containing the same. At the same time, the artificial turf designed in the present invention does not require drilling with an electric trowel, and not only can it prevent the growth of natural weeds, but also can avoid problems such as wear of the bottom adhesive layer caused by leakage of quartz sand during paving. The manufacturing method of the present invention is simple, can save manpower and reduce costs, and is favorable for market popularization and industrialized production.
[0006] In order to achieve the above object, a first object of the present invention is to provide a highly water-permeable base fabric.
[0007] The highly water-permeable base fabric is woven by alternating warp and weft threads, and the warp and / or weft threads include thread A having a thickness of 0.08-0.5 mm.
[0008] The beneficial effects of the above technical solutions include at least the following: if the yarn thickness is less than 0.08mm, the yarn is too thin during the weaving process, and the yarn cannot be expanded at the intersection of the warp and weft yarns to form effective holes and satisfy the water permeability; if the yarn thickness is more than 0.5mm, the yarn cannot be cut and drawn to ensure stable production, and the yarn is too thick to be weaved afterwards.
[0009] Furthermore, the thickness of the thread A is preferably 0.1-0.3 mm.
[0010] Preferably, the warp and / or weft yarns comprise yarn B having a thickness of 0.03-0.06 mm.
[0011] Preferably, the warp yarn is yarn B and the weft yarn is yarn A.
[0012] Preferably, the warp yarn is yarn B, the weft yarn is yarn A and B, and the weft yarns are woven in an alternating arrangement in an ABAB fashion, or in other regular or irregular fashion.
[0013] Preferably, the weft yarn is yarn B and the warp yarn is yarn A.
[0014] Preferably, the weft yarn is yarn B, the warp yarns are yarns A and B, and the warp yarns are woven in an alternating arrangement in an ABAB fashion, or in other regular or irregular fashion.
[0015] Furthermore, the warp yarns are one type of thickness, the weft yarns are three types of thickness, and the weft yarns are arranged and woven in a regular or irregular manner; Or, the weft yarns are one type of thickness, and the warp yarns are three types of thickness, and the warp yarns are arranged and woven in a regular or irregular manner; Alternatively, the warp yarns have two thicknesses and the weft yarns have three thicknesses, and the warp yarns and the weft yarns are arranged and woven in a regular or irregular manner; Alternatively, the weft yarns have two different thicknesses, the warp yarns have three different thicknesses, and the warp yarns and the weft yarns are arranged in a regular or irregular manner and woven together. In other words, any knitting method in which yarns of appropriate different thicknesses are selected, arranged in a regular or irregular manner, woven together, and effective holes are formed between the yarns to improve water permeability is within the scope of the present invention.
[0016] Preferably, both the warp and weft threads are thread A.
[0017] Preferably, the width of the warp threads is 0.5-3 mm; The width of the weft yarn is 0.5-4 mm; The weave density of the warp yarn is 400-2400 yarns / meter; The weave density of the weft yarns is 300-2400 threads / meter.
[0018] The beneficial effects of the above technical solutions include at least the following: if the warp or weft width is less than 0.5mm, a dimensionally stable base fabric cannot be woven; if the warp width is more than 3mm or the weft width is more than 4mm, the yarns are too wide, so folding phenomenon occurs during weaving, and the flatness of the base fabric cannot be guaranteed, so it cannot be produced; if the warp weaving density is less than 400 threads / meter and the weft weaving density is less than 300 threads / meter, the produced base fabric has low dimensional stability and cannot meet the requirements for use; if the warp weaving density is more than 2400 threads / meter and the weft weaving density is more than 2400 threads / meter, thin threads need to be combined for weaving production, which also causes dimensional stability problems.
[0019] Furthermore, the width of the warp yarn is 1-2 mm; The width of the weft is 1-3mm, The weave density of the warp yarn is 600-1200 yarns / meter; The weave density of the weft yarns is 400-1200 threads / meter.
[0020] Preferably, the colour of the thread is one or more of the following: black, green, white, blue, purple, orange, yellow and brown.
[0021] The second object of the present invention is to (1) homogeneously mixing one or more of polyethylene resin, polypropylene resin, polyamide resin, and polyethylene terephthalate resin with a color master batch and a processing aid, extruding the mixture with a screw extruder, cutting it, drawing it into a yarn of a desired width and thickness, and winding it up after forming it into a desired shape for use; (2) to provide a method for producing a highly water-permeable base fabric, the method including a step of placing the warp and weft threads on a knitting machine according to a designed weaving density and arrangement method, thereby obtaining a desired highly water-permeable base fabric.
[0022] A third object of the present invention is to provide a highly water-permeable and durable artificial turf comprising a base fabric including the highly water-permeable base fabric, pile tufted onto the base fabric, and a bottom adhesive applied to the bottom surface of the base fabric.
[0023] Preferably, the base fabric is one layer of the highly water-permeable base fabric, Or, the base fabric is a combination of one layer of the highly water-permeable base fabric and one layer of mesh cloth, Alternatively, the base fabric is a combination of the highly water-permeable base fabric and any nonwoven fabric.
[0024] Preferably, the bottom adhesive is composed of an original glue, a filler, and a foaming agent; The original glue is one or more selected from a styrene-butadiene adhesive, a styrene-propylene adhesive, an ethylene-vinyl acetate adhesive, an acrylic adhesive, an epoxy adhesive, and a polyurethane adhesive; The mass ratio of the original glue to the filler is 8:2-2:8; The foaming agent is 0.3%-0.7% of the total mass of the original glue and filler; In addition, in the adhesive bottom coating process, the density of the adhesive after foaming is controlled to be 0.8-0.2 times the density of the adhesive before foaming.
[0025] The beneficial effects of the above technical solutions include at least the following: The purpose of adding a foaming agent to the adhesive is to make the adhesive easier to foam, the foaming more stable, the foam finer, and form a sufficient amount of interconnected pores inside the adhesive layer after curing, which helps to improve the water permeability of the adhesive layer.
[0026] If the ratio of original glue to filler is greater than 8:2, there is too much original glue, and the adhesive film after subsequent curing will be too dense, which will have a negative impact on the water permeability of the entire lawn; if the amount of foaming agent added is less than 0.3%, the foaming property of the adhesive will be so low that it cannot reach the ideal foaming density; if the foaming density ratio is greater than 0.8, there will be insufficient holes inside the adhesive layer, which will have a negative impact on water permeability; on the other hand, if the ratio of original glue to filler is less than 2:8, the amount of foaming agent added is greater than 0.7%, and the foaming density ratio is less than 0.2, there will be many holes in the adhesive film layer after subsequent curing, which can ensure high water permeability of the entire lawn, but there will be too much filler and low density, which will have a negative impact on the mechanical performance of the bottom adhesive layer of the lawn.
[0027] Furthermore, the mass ratio of the original glue to the filler is 7:3-3:7; The foaming agent is 0.4%-0.6% of the total mass of the original glue and filler; In addition, in the adhesive bottom coating process, the density of the adhesive after foaming is controlled to be 0.7-0.3 times the density of the adhesive before foaming.
[0028] Preferably, the foaming agent is one or more selected from sodium dodecyl sulfate, sodium dodecyl sulfonate, sodium dodecyl benzene sulfonate, sodium dodecyl diphenyl ether disulfonate, sodium α-alkenyl sulfonate, and sodium rosinate; The filler is one or more selected from calcium carbonate, barium sulfate, mica powder, aluminum hydroxide, talc powder, and silica.
[0029] Furthermore, the adhesive formulation components for the bottom adhesive may include one or more color pastes selected from black paste, red paste, green paste, orange paste, blue paste, and purple paste, and one or more thickeners selected from polyacrylic acid-based, cellulose-based, and polyurethane-based thickeners. The color paste is added to color the bottom adhesive layer to meet the color needs of different customers, and the thickener is added to adjust the viscosity of the adhesive to make it less likely to leak when preparing the bottom adhesive.
[0030] A fourth object of the present invention is to 1) a wire drawing process in which a polyethylene resin and / or a polypropylene resin, a color master batch, and an auxiliary are uniformly mixed to form a mixture, and the mixture is extruded by a single screw extruder to form a wire and processed into an artificial pile; 2) a tufting process in which the twisted artificial pile is tufted into a base fabric at a predetermined row pitch and gauge using a tufting machine to form a semi-finished artificial turf product; 3) To provide a method for manufacturing highly water-permeable and durable artificial turf, which includes an adhesive bottom application process, in which an adhesive is applied to the bottom surface of a semi-finished artificial turf product and then cured in an oven to obtain the artificial turf.
[0031] As described above, the highly water-permeable base fabric designed in the present invention can form effective holes at the intersections of the warp and weft threads by designing the warp and weft threads with appropriate width and thickness, and weaving them according to a combination method and a certain density, thereby improving the water permeability of the base fabric. At the same time, when the highly water-permeable base fabric designed in the present invention is applied to artificial turf, a highly water-permeable artificial turf can be produced, which does not require drilling with an electric trowel, and effectively avoids the problems of natural weeds growing during subsequent use and quartz sand leakage during paving. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0032] The technical solutions in the embodiments of the present invention are described below clearly and completely, and it is clear that the described embodiments are only some embodiments of the present invention, and are not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative labor fall within the protection scope of the present invention.
[0033] Example 1 The manufacture of highly water permeable base fabric is (1) uniformly mixing 88 parts by mass of polypropylene, 10 parts by mass of color master batch, and 2 parts by mass of auxiliary agent, extruding the mixture through a screw extruder, and then cutting and drawing the extrudate; Here, the thickness of the weft is 0.08 mm and the width is 1.5 mm, The warp threads are 0.04 mm thick and 1.5 mm wide. After being shaped, they are wound up and ready for use. (2) placing the warp and weft threads on a knitting machine at a weaving density of 780 threads per meter to weave the fabric, thereby obtaining the desired highly water-permeable base fabric.
[0034] The production of highly water-permeable and durable artificial turf is 1) uniformly mixing 85 parts by mass of polyethylene, 10 parts by mass of color master batch, and 5 parts by mass of auxiliary agent, extruding the mixture by a screw extruder, drawing the wire, and processing it into an artificial pile; 2) tufting the twisted artificial pile into a highly water-permeable base fabric at a predetermined row pitch and gauge using a tufting machine to form a semi-finished artificial turf product; 3) Stirring and mixing the styrene butadiene original glue and calcium carbonate in a mass ratio of 5:5, obtaining a finished adhesive after 30 minutes, then adding sodium dodecyl sulfate of 0.5% of the total mass of the finished adhesive, and continuing to stir for 10 minutes to obtain a finished adhesive, adjusting the process parameters in a foaming machine to foam the finished adhesive, controlling the density after foaming to be 0.5 times the density before foaming, applying the foamed adhesive to the bottom part of the artificial turf semi-finished product, and curing it in an oven to obtain a highly water-permeable and durable artificial turf.
[0035] Example 2 Example 2 is similar to Example 1, except that the weft yarn in step (1) has a thickness of 0.1 mm and a width of 1.5 mm.
[0036] Example 3 Example 3 is similar to Example 1, except that the weft yarn in step (1) has a thickness of 0.2 mm and a width of 1.5 mm.
[0037] Example 4 Example 4 is similar to Example 1, except that the weft yarn in step (1) has a thickness of 0.3 mm and a width of 1.5 mm.
[0038] Example 5 Example 5 is similar to Example 1, except that the weft yarn in step (1) has a thickness of 0.4 mm and a width of 1.5 mm.
[0039] Example 6 Example 6 is similar to Example 1, except that the weft yarn in step (1) has a thickness of 0.5 mm and a width of 1.5 mm.
[0040] Comparative Example 1 Comparative Example 1 is similar to Example 1, except that the weft yarn in step (1) has a thickness of 0.04 mm and a width of 1.5 mm.
[0041] Comparative Example 2 Comparative Example 2 is similar to Example 1, except that the thickness of the weft yarn in step (1) is 0.06 mm and the width is 1.5 mm.
[0042] Comparative Example 3 The manufacture of highly water permeable base fabric is (1) uniformly mixing 88 parts by mass of polypropylene, 10 parts by mass of color master batch, and 2 parts by mass of auxiliary agent, extruding the mixture with a screw extruder, cutting it, drawing it into a weft having a thickness of 0.6 mm and a width of 1.5 mm, and a warp having a thickness of 0.04 mm and a width of 1.5 mm, and winding it up after shaping it for use; (2) placing the warp and weft threads on a knitting machine at a weaving density of 780 threads per meter;
[0043] Because the thickness of the weft yarn is too thick, it is not possible to guarantee stable production of a highly water-permeable base fabric.
[0044] Comparative Example 4 The manufacture of artificial turf base fabrics is (1) uniformly mixing 88 parts by mass of polypropylene, 10 parts by mass of color master batch, and 2 parts by mass of auxiliary agent, extruding the mixture through a screw extruder, cutting it, drawing it into a weft having a thickness of 0.04 mm and a width of 1.5 mm, and a warp having a thickness of 0.04 mm and a width of 1.5 mm, and winding it up after shaping it for use; (2) placing the warp and weft yarns on a knitting machine with a weaving density of 780 threads per meter to weave the desired artificial turf base fabric.
[0045] The production of artificial turf 1) uniformly mixing 85 parts by mass of polyethylene, 10 parts by mass of color master batch, and 5 parts by mass of auxiliary agent, extruding the mixture by a screw extruder, drawing the wire, and processing it into an artificial pile; 2) tufting the twisted artificial pile into a base fabric at a predetermined row pitch and gauge using a tufting machine to form a semi-finished artificial turf product; 3) Stirring and mixing the styrene butadiene original glue and calcium carbonate in a 5:5 ratio, obtaining the finished adhesive after 30 minutes, applying the finished adhesive to the bottom of the semi-finished grass, and curing it in an oven to obtain artificial grass; 4) Perforating the manufactured artificial turf according to the 10cm x 10cm standard.
[0046] Permeability test: The water permeability of all samples was tested according to the methods in the FIFA Quality Programme for Football Turf-2015.
[0047] Before testing, the test samples were left in an environment of 23±2°C for at least 4 h.
[0048] The test sample is clamped between two metal or plastic rings with an inner diameter of 300mm±2mm, and a supporting grid is placed under the clamped sample to prevent the sample from being compressed and deformed by a large amount of water during the permeability test. The grid must ensure that the maximum deformation from the outside to the center of the ring is less than 5mm. After clamping, the slits are sealed with a sealant to prevent water leakage. After the test device is manufactured, 5L of water is poured into the rings to wet the test sample and check whether the test device has a water leakage phenomenon. If there is a water leakage phenomenon, the device must be sealed again. This leakage test process must be carried out for at least 30 minutes.
[0049] After the preparation work is completed, it is necessary to ensure that the test equipment is in a horizontal state before starting the test. Then, inject a large amount of water into the equipment to ensure that the water level is 70-90mm above the bottom height of the sample being tested. When the water level drops to a point 30mm away from the bottom height, start timing. Record the time it takes for the water level to drop from the 30mm point to the 10mm point. The accuracy is 0.1 seconds. If the water permeability rate is slow, the test should be stopped at 30 minutes.
[0050] The above procedure was repeated two more times and the last two results were averaged.
[0051] The permeability rate (I c ) was calculated. I c =F wc / t c however, F wc is the height (mm) that the water level drops, usually 20 mm, t c is the time (h) until the water level drops to a certain height, How to determine permeability: At present, the lawns normally produced in the industry need to be drilled with an electric trowel after the adhesive bottom coating process to solve the water permeability problem, and when the water permeability of such lawns is tested according to the FIFA detection method, the water permeability is between 8000-12000mm / h, which can basically meet the demand, but in order to avoid the problem of large amounts of water puddling when encountering scenes such as heavy rain, the water permeability needs to reach 15000mm / h or more. Therefore, lawns with a water permeability of 15000mm / h or more are considered to be high water permeability lawns.
[0052] Durability Test: Initial extraction force: The test is carried out according to the method in standard ISO4919 by electronic universal testing machine, specifically, a newly produced test sample block of 20cm*20cm is cut out and left in an environment of relative humidity (65±4)% and temperature (20±2)℃ for 24h, the test sample block is placed in the electronic universal testing machine, the half-cluster pile is clamped with a clamp in the direction perpendicular to the sample block, the equipment is started, and the maximum force value after the pile is completely extracted is recorded as the extraction force value of the pile, and the extraction force value of each sample block is the average value based on the data of 10 samples.
[0053] Extraction force after long term use: Simulating the actual use of the lawn, a newly manufactured test sample block of 40cm*80cm was subjected to a rolling abrasion test using the Lisport abrasion tester, 3kg of gravel was filled into the bottom of the lawn, and the abrasion test was stopped after 30,000 rotations of rolling, 100kg of water was poured into the test sample, and the Lisport abrasion tester continued to perform the rolling test of 30,000 rotations after the abrasion test was completed, and 100kg of water was poured into the test sample, and the Lisport abrasion tester continued to perform the rolling test of 30,000 rotations after the abrasion test was completed, and the water permeation and abrasion tests were performed sequentially according to this method until the abrasion test reached a total of 300,000 rotations. After the simulation test, the pull-out force test was performed according to the method in ISO4919.
[0054] Bottom coating after long-term use: After simulating long-term use of the samples, the coating condition of the adhesive layer on the bottom surface was observed, and samples with good bottom coating and no adhesive layer peeling were rated as ☆☆☆☆, samples with average bottom coating and partial adhesive layer peeling were rated as ☆☆☆, and samples with poor bottom coating and most of the adhesive layer peeling were rated as ☆☆.
[0055] According to the above water permeability test and durability test methods, relevant tests were carried out for Examples 1-6 and Comparative Examples 1, 2, and 4. The results are shown in Table 1.
[0056] Table 1 JPEG2025503354000001.jpg67170
[0057] As can be seen from Examples 1 to 6 in Table 1, when the weft thickness is selected to be 0.08-0.5mm, the artificial turf produced has good water permeability, and when the simulation test of the actual use of the artificial turf is carried out, it does not make holes and has good water permeability at the same time, so that the bottom coverage condition and mechanical performance after the simulation test are both good, and especially when the weft thickness is 0.1-0.3mm, the mechanical performance after the simulation test is excellent. The reason why Examples 5 and 6 have poor coverage condition and mechanical performance after long-term use compared to other Examples is mainly because the weft thickness is too thick, the gaps in the base fabric are too large, and some of the quartz sand leaks out.
[0058] In Comparative Example 1 and Comparative Example 2, the thickness of the weft is less than 0.08 mm, so no effective holes are formed where the warp and weft cross, resulting in poor water permeability, and when a simulation test of the actual usage of artificial turf is conducted, the artificial turf is left in a puddle state for a long time, which accelerates the deterioration of the bottom adhesive layer, resulting in poor bottom coverage and mechanical performance after long-term use. In Comparative Example 4, even though the turf has a certain degree of water permeability, the existence of holes made by the electric trowel causes a large amount of quartz sand to leak to the bottom, so the bottom wear is significant during use, and the coverage and mechanical performance are both poor.
[0059] Example 7 Example 7 is similar to Example 1, except that the weft yarn in step (1) has a thickness of 0.25 mm and a width of 1.5 mm, and the warp yarn has a thickness of 0.04 mm and a width of 1.5 mm.
[0060] Example 8 Example 8 is similar to Example 1, except that in step (1), weft yarns of two different thicknesses, 0.25 mm and 1.5 mm in width and 0.04 mm and 1.5 mm in width, and warp yarns of one different thickness, 0.04 mm and 1.5 mm in width, are drawn, and in step (2), the weft yarns of the two different thicknesses are arranged alternately and woven to obtain a highly water permeable base fabric.
[0061] Example 9 Example 9 is similar to Example 1, except that in step (1), the warp yarns are drawn to a thickness of 0.25 mm and a width of 1.5 mm, and the weft yarns are drawn to a thickness of 0.04 mm and a width of 1.5 mm.
[0062] Example 10 Example 10 is similar to Example 1, except that in step (1), warp yarns of two thicknesses, 0.25 mm and 1.5 mm in width and 0.04 mm and 1.5 mm in width, and weft yarns of one thickness, 0.04 mm and 1.5 mm in width, are drawn, and in step (2), the warp yarns of the two thicknesses are arranged alternately and woven to obtain a highly water permeable base fabric.
[0063] Example 11 Example 11 is similar to Example 1, except that in step (1), the warp yarns are drawn to a thickness of 0.25 mm and a width of 1.5 mm, and the weft yarns are drawn to a thickness of 0.25 mm and a width of 1.5 mm.
[0064] According to the above water permeability test and durability test methods, the relevant tests were carried out for Examples 7-11, and the results are shown in Table 2.
[0065] Table 2 JPEG2025503354000002.jpg49170
[0066] As can be seen from Examples 7-11 in Table 2, the thickness of the selected warp and weft yarns is 0.08-0.5mm, and the artificial turf produced by weaving according to the arrangement combination method in the examples has excellent water permeability, and the bottom coverage condition and mechanical performance after the simulation test are both good.
[0067] Example 12 Example 12 is similar to Example 1, except that in step (1), the warp yarns are drawn to a thickness of 0.04 mm and a width of 0.5 mm, and the weft yarns are drawn to a thickness of 0.25 mm and a width of 2 mm, and in step (2), the warp yarns and the weft yarns are woven on a knitting machine according to a weaving density of 2,400 warp yarns per meter and 550 weft yarns per meter to obtain the desired highly water-permeable base fabric.
[0068] Example 13 Example 13 is similar to Example 1, except that in step (1), the warp yarns are drawn to a thickness of 0.04 mm and a width of 1 mm, and the weft yarns are drawn to a thickness of 0.25 mm and a width of 2 mm, and in step (2), the warp yarns and the weft yarns are woven on a knitting machine according to a weaving density of 1,200 warp yarns per meter and 550 weft yarns per meter to obtain the desired highly water-permeable base fabric.
[0069] Example 14 Example 14 is similar to Example 1, except that in step (1), the warp yarns are drawn to a thickness of 0.04 mm and a width of 2 mm, and the weft yarns are drawn to a thickness of 0.25 mm and a width of 2 mm, and in step (2), the warp yarns and the weft yarns are placed on a knitting machine and woven according to a weaving density of 600 warp yarns per meter and 550 weft yarns per meter to obtain the desired highly water permeable base fabric.
[0070] Example 15 Example 15 is similar to Example 1, except that in step (1), the warp yarns are drawn to a thickness of 0.04 mm and a width of 3 mm, and the weft yarns are drawn to a thickness of 0.25 mm and a width of 2 mm, and in step (2), the warp yarns and the weft yarns are placed on a knitting machine and woven according to a weaving density of 400 warp yarns per meter and 550 weft yarns per meter to obtain the desired highly water permeable base fabric.
[0071] Example 16 Example 16 is similar to Example 1, except that in step (1), the warp yarns are drawn to a thickness of 0.25 mm and a width of 2 mm, and the weft yarns are drawn to a thickness of 0.04 mm and a width of 0.5 mm, and in step (2), the warp yarns and the weft yarns are placed on a knitting machine and woven according to a weaving density of 600 warp yarns per meter and 2,400 weft yarns per meter to obtain the desired highly water-permeable base fabric.
[0072] Example 17 Example 17 is similar to Example 1, except that in step (1), the warp yarns are drawn to a thickness of 0.25 mm and a width of 2 mm, and the weft yarns are drawn to a thickness of 0.04 mm and a width of 1 mm, and in step (2), the warp yarns and the weft yarns are woven on a knitting machine according to a weaving density of 600 warp yarns per meter and 1,200 weft yarns per meter to obtain the desired highly water-permeable base fabric.
[0073] Example 18 Example 18 is similar to Example 1, except that in step (1), the warp yarns are drawn to a thickness of 0.25 mm and a width of 2 mm, and the weft yarns are drawn to a thickness of 0.04 mm and a width of 3 mm, and in step (2), the warp yarns and the weft yarns are placed on a knitting machine and woven according to a weaving density of 600 warp yarns per meter and 400 weft yarns per meter to obtain the desired highly water permeable base fabric.
[0074] Example 19 Example 19 is similar to Example 1, except that in step (1), the warp yarns are drawn to a thickness of 0.25 mm and a width of 2 mm, and the weft yarns are drawn to a thickness of 0.04 mm and a width of 4 mm, and in step (2), the warp yarns and the weft yarns are woven on a knitting machine at a weaving density of 600 warp yarns per meter and 300 weft yarns per meter to obtain the desired highly water permeable base fabric.
[0075] According to the above water permeability test and durability test methods, the relevant tests were carried out for Examples 12-19, and the results are shown in Table 3.
[0076] Table 3 JPEG2025503354000003.jpg118170
[0077] As can be seen from Examples 12-15 in Table 3, when the selected warp width is 0.5-3mm and the weave density of the warp is 400-2400 threads / meter, the manufactured highly water-permeable and durable artificial turf has excellent water permeability, and the bottom coverage and mechanical performance after the simulation test are both good. In particular, when the warp width is 1-2mm and the weave density of the warp is 600-1200 threads / meter, the manufactured artificial turf not only has excellent water permeability and mechanical performance after the simulation test, but also has excellent dimensional stability.
[0078] As can be seen from Examples 16-19 in Table 3, when the selected weft width is 0.5-4mm and the weaving density of the weft is 300-2400 threads / meter, the manufactured highly water-permeable and durable artificial turf has excellent water permeability, and the bottom coverage and mechanical performance after the simulation test are both good. In particular, when the warp width is 1-3mm and the weaving density of the warp is 400-1200 threads / meter, the manufactured artificial turf not only has excellent water permeability and mechanical performance after the simulation test, but also has excellent dimensional stability.
[0079] Example 20 In Example 20, in step (1), drawing is performed to obtain a weft having a thickness of 0.25 mm and a width of 1.5 mm and a warp having a thickness of 0.04 mm and a width of 1.5 mm; Step 3) is the same as Example 1, except that the styrene butadiene original glue and calcium carbonate are stirred and mixed in a mass ratio of 8:2.
[0080] Example 21 In Example 21, in step (1), a weft having a thickness of 0.25 mm and a width of 1.5 mm and a warp having a thickness of 0.04 mm and a width of 1.5 mm are drawn; Step 3) is the same as Example 1, except that the styrene butadiene original glue and calcium carbonate are stirred and mixed in a mass ratio of 7:3.
[0081] Example 22 In Example 22, in step (1), drawing is performed to obtain a weft having a thickness of 0.25 mm and a width of 1.5 mm and a warp having a thickness of 0.04 mm and a width of 1.5 mm; Step 3) is the same as Example 1, except that the styrene butadiene original glue and calcium carbonate are stirred and mixed in a mass ratio of 3:7.
[0082] Example 23 In Example 23, in step (1), drawing is performed to obtain a weft having a thickness of 0.25 mm and a width of 1.5 mm and a warp having a thickness of 0.04 mm and a width of 1.5 mm; Step 3) is the same as Example 1, except that the styrene butadiene original glue and calcium carbonate are stirred and mixed in a mass ratio of 2:8.
[0083] Comparative Example 5 In Comparative Example 5, in step (1), the weft yarn is drawn to a thickness of 0.25 mm and a width of 1.5 mm, and the warp yarn is drawn to a thickness of 0.04 mm and a width of 1.5 mm; Step 3) is the same as Example 1, except that the styrene butadiene original glue and calcium carbonate are stirred and mixed in a mass ratio of 9:1.
[0084] Comparative Example 6 In Comparative Example 6, in step (1), the weft yarn is drawn to a thickness of 0.25 mm and a width of 1.5 mm, and the warp yarn is drawn to a thickness of 0.04 mm and a width of 1.5 mm; Step 3) is the same as Example 1, except that the styrene butadiene original glue and calcium carbonate are stirred and mixed in a mass ratio of 1:9.
[0085] According to the above water permeability test and durability test methods, the relevant tests were carried out for Examples 20-23 and Comparative Examples 5-6, and the results are shown in Table 4.
[0086] Table 4 JPEG2025503354000004.jpg101170
[0087] As can be seen from Examples 20-23 in Table 4, when the mixing ratio of original glue and filler is between 8:2-2:8, the manufactured artificial turf has good water permeability, and the bottom coverage condition and mechanical performance after the simulation test are both good.
[0088] As can be seen from Comparative Example 5, when the mixing ratio of original glue to filler is greater than 8:2, the amount of original glue is too much, so the adhesive film after later hardening is too dense, which adversely affects the water permeability of the entire lawn and the mechanical performance after the simulation test of the lawn. As can be seen from Comparative Example 6, when the mixing ratio of original glue to filler is less than 2:8, the amount of filler is too much, which adversely affects the mechanical performance of the adhesive layer, resulting in low pull-out force before and after the simulation of the lawn and poor coverage of the bottom surface after the simulation test.
[0089] Example 24 In Example 24, in step (1), drawing is performed to obtain a weft having a thickness of 0.25 mm and a width of 1.5 mm and a warp having a thickness of 0.04 mm and a width of 1.5 mm; In step 3), sodium dodecyl sulfate is added as a foaming agent in an amount of 0.3% by weight of the finished adhesive, and the mixture is stirred for 10 minutes to obtain the finished adhesive. The process parameters are adjusted in a foaming machine to foam the finished adhesive, and the density after foaming is controlled to be 0.8 times that before foaming. The foamed adhesive is applied to the bottom of the semi-finished turf and cured in an oven to obtain a highly water-permeable and durable artificial turf, except that the process is the same as in Example 1.
[0090] Example 25 In Example 25, in step (1), drawing is performed to obtain a weft having a thickness of 0.25 mm and a width of 1.5 mm and a warp having a thickness of 0.04 mm and a width of 1.5 mm; In step 3), sodium dodecyl sulfate is added as a foaming agent in an amount of 0.4% of the total amount of the finished adhesive, and the mixture is stirred for 10 minutes to obtain the finished adhesive. The process parameters are adjusted in the foaming machine to foam the finished adhesive, and the density after foaming is controlled to be 0.7 times that before foaming. The foamed adhesive is applied to the bottom of the semi-finished turf and cured in an oven to obtain a highly water-permeable and durable artificial turf, except that the process is the same as in Example 1.
[0091] Example 26 In Example 26, in step (1), drawing is performed to obtain a weft having a thickness of 0.25 mm and a width of 1.5 mm and a warp having a thickness of 0.04 mm and a width of 1.5 mm; In step 3), sodium dodecyl sulfate is added as a foaming agent in an amount of 0.6% of the total amount of the finished adhesive, and the mixture is stirred for 10 minutes to obtain the finished adhesive. The process parameters are adjusted in the foaming machine to foam the finished adhesive, and the density after foaming is controlled to be 0.3 times that before foaming. The foamed adhesive is applied to the bottom of the semi-finished turf and cured in an oven to obtain a highly water-permeable and durable artificial turf, except that the process is the same as in Example 1.
[0092] Example 27 In Example 27, in step (1), drawing is performed to obtain a weft having a thickness of 0.25 mm and a width of 1.5 mm and a warp having a thickness of 0.04 mm and a width of 1.5 mm; In step 3), sodium dodecyl sulfate is added as a foaming agent in an amount of 0.7% of the total amount of the finished adhesive, and the mixture is stirred for 10 minutes to obtain the finished adhesive. The process parameters are adjusted in the foaming machine to foam the finished adhesive, and the density after foaming is controlled to be 0.2 times that before foaming. The foamed adhesive is applied to the bottom of the semi-finished turf and cured in an oven to obtain a highly water-permeable and durable artificial turf, except that the process is the same as in Example 1.
[0093] Comparative Example 7 In Comparative Example 7, in step (1), the wire is drawn into a weft having a thickness of 0.25 mm and a width of 1.5 mm and a warp having a thickness of 0.04 mm and a width of 1.5 mm; In step 3), sodium dodecyl sulfate is added as a foaming agent in an amount of 0.1% of the total amount of the finished adhesive, and the mixture is stirred for 10 minutes to obtain the finished adhesive. The process parameters are adjusted in the foaming machine to foam the finished adhesive, and the density after foaming is controlled to be 0.9 times that before foaming. The foamed adhesive is applied to the bottom of the semi-finished grass, and cured in an oven to obtain the artificial turf, except that the process is the same as in Example 1.
[0094] Comparative Example 8 In Comparative Example 8, in step (1), the weft yarn is drawn to a thickness of 0.25 mm and a width of 1.5 mm, and the warp yarn is drawn to a thickness of 0.04 mm and a width of 1.5 mm; In step 3), sodium dodecyl sulfate is added as a foaming agent in an amount of 0.9% of the total amount of the finished adhesive, and the mixture is stirred for 10 minutes to obtain the finished adhesive. The process parameters are adjusted in the foaming machine to foam the finished adhesive, and the density after foaming is controlled to be 0.1 times that before foaming. The foamed adhesive is applied to the bottom of the semi-finished grass, and cured in an oven to obtain the artificial turf, except that the process is the same as in Example 1.
[0095] According to the above water permeability test and durability test methods, the relevant tests were carried out for Examples 24-27 and Comparative Examples 7-8, and the results are shown in Table 5.
[0096] Table 5 JPEG2025503354000005.jpg113170
[0097] As can be seen from Examples 24-27 in Table 5, when the density ratio value of the adhesive after foaming to the adhesive before foaming is between 0.8-0.2 and the amount of foaming agent added is between 0.3%-0.7%, the artificial turf produced has good water permeability, and the bottom coverage condition and mechanical performance after the simulation test are both good. Especially when the density ratio value is between 0.7-0.3 and the amount of foaming agent added is between 0.4%-0.6%, each performance after the simulation test is excellent.
[0098] As can be seen from Comparative Example 7, when the density ratio value of the adhesive after foaming and the adhesive before foaming is greater than 0.8 and the amount of foaming agent added is less than 0.3%, the bottom adhesive layer is relatively dense and does not have a sufficient amount of holes, resulting in low water permeability and poor mechanical performance after the lawn simulation test. As can be seen from Comparative Example 8, when the density ratio value of the adhesive after foaming and the adhesive before foaming is less than 0.2 and the amount of foaming agent added is greater than 0.7%, the foaming is too much, so the holes in the bottom adhesive layer are too many, and the lawn has good water permeability, but the mechanical performance of the bottom adhesive layer is very poor.
[0099] Example 28 Example 28 is similar to Example 7, except that the warp thickness in step (1) is 0.03 mm.
[0100] Example 29 Example 29 is similar to Example 7, except that the warp thickness in step (1) is 0.06 mm.
[0101] According to the above water permeability test and durability test methods, the relevant tests were carried out on Examples 28-29, and the results are shown in Table 6.
[0102] Table 6 JPEG2025503354000006.jpg44170
[0103] As can be seen from the examples in Table 6, the manufactured artificial turf has good water permeability, and when conducting a simulation test of the actual usage conditions of the artificial turf, no holes are drilled and at the same time it has good water permeability, so the bottom coverage condition and mechanical performance after the simulation test are both good.
[0104] Example 30 Example 30 is similar to Example 7, except that in step 3) the original glue is a styrene propylene adhesive.
[0105] Example 31 Example 31 is similar to Example 7, except that in step 3) the original glue is an acrylic adhesive.
[0106] Example 32 Example 32 is the same as Example 7, except that in step 3), the original glue is styrene butadiene adhesive and styrene propylene adhesive, and the mass ratio is 1:1.
[0107] Example 33 Example 33 is similar to Example 7, except that in step 3), the original glue is a styrene butadiene adhesive and the filler is aluminum hydroxide.
[0108] Example 34 Example 34 is the same as Example 7, except that in step 3), the original glue is styrene butadiene adhesive and the filler is mica powder.
[0109] According to the above water permeability test and durability test methods, the relevant tests were carried out for Examples 30-34, and the results are shown in Table 7.
[0110] Table 7 JPEG2025503354000007.jpg84170
[0111] As can be seen from the examples in Table 7, when the mixing ratio of the original glue and filler is changed, the manufactured artificial turf has good water permeability, and the bottom coverage condition and mechanical performance after the simulation test are both good.
[0112] In this specification, each embodiment will be described step by step, and each embodiment will be described focusing on the differences from other embodiments, and reference may be made alternately to the same and similar parts between each embodiment.
[0113] The above description of the disclosed embodiments enables one skilled in the art to realize or use the present invention. Various modifications to the above embodiments will be apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Thus, the present invention is not intended to be limited to these embodiments shown herein, but is to be accorded the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A highly water-permeable base fabric, characterized in that the warp threads and the weft threads are woven in an alternating manner, and the warp threads and / or the weft threads include thread A having a thickness of 0.08-0.5 mm.
2. The highly water-permeable base fabric according to claim 1, characterized in that the warp yarns and / or weft yarns include yarn B having a thickness of 0.03-0.06 mm.
3. The highly water-permeable base fabric according to claim 2, characterized in that the warp yarn is yarn B and the weft yarn is yarn A.
4. The highly water-permeable base fabric according to claim 2, wherein the warp yarn is yarn B, the weft yarn is yarn A and yarn B, and the weft yarns are woven in an alternating arrangement in an ABAB manner.
5. The highly water-permeable base fabric according to claim 2, characterized in that the weft yarn is yarn B and the warp yarn is yarn A.
6. The highly water-permeable base fabric according to claim 2, wherein the weft yarn is yarn B, the warp yarns are yarns A and B, and the warp yarns are woven in an alternating arrangement in an ABAB manner.
7. The highly water-permeable base fabric according to claim 1, wherein the warp yarns and the weft yarns are both thread A.
8. The width of the warp threads is 0.5-3 mm; The width of the weft yarn is 0.5-4 mm; The weave density of the warp yarns is 400-2400 yarns / meter; The highly water-permeable base fabric according to claim 1, characterized in that the weft density is 300-2400 threads / meter.
9. The highly water-permeable base fabric according to any one of claims 1 to 8, characterized in that the color of the yarn is one or more of black, green, white, blue, purple, orange, yellow and brown.
10. A method for producing the highly water permeable base fabric according to claim 9, (1) uniformly mixing one or more of polyethylene resin, polypropylene resin, polyamide resin, and polyethylene terephthalate resin with a color master batch and a processing aid, extruding the mixture with a screw extruder, cutting the extrudate, drawing the extrudate into a yarn of a desired width and thickness, and winding the extrudate into a desired shape for use; (2) A step of placing the warp yarns on a knitting machine according to the designed weaving density and arrangement method to obtain a desired highly water permeable base fabric.
11. A highly water-permeable and durable artificial turf comprising a base fabric comprising the highly water-permeable base fabric according to any one of claims 1 to 9, pile tufted onto the base fabric, and a bottom adhesive applied to the bottom surface of the base fabric.
12. The base fabric is one layer of the highly water-permeable base fabric, Or, the base fabric is a combination of one layer of the highly water-permeable base fabric and one layer of mesh cloth, Alternatively, the highly water-permeable and durable artificial turf according to claim 11, characterized in that the base fabric is a combination of the highly water-permeable base fabric and any nonwoven fabric.
13. The bottom adhesive is composed of original glue, filler, and foaming agent, The original glue is one or more selected from a styrene-butadiene adhesive, a styrene-propylene adhesive, an ethylene-vinyl acetate adhesive, an acrylic adhesive, an epoxy adhesive, and a polyurethane adhesive; The mass ratio of the original glue to the filler is 8:2-2:8; The foaming agent is 0.3%-0.7% of the total mass of the original glue and filler; The highly water-permeable and durable artificial turf according to claim 11, characterized in that in the adhesive bottom application process, the density of the adhesive after foaming is controlled to be 0.8-0.2 times the density of the adhesive before foaming.
14. A method for producing a highly water-permeable and durable artificial turf according to claim 12 or 13, 1) a wire drawing process in which a polyethylene resin and / or a polypropylene resin, a color master batch, and an auxiliary are uniformly mixed to form a mixture, and the mixture is extruded by a single screw extruder to form a wire and processed into an artificial pile; 2) a tufting step in which the twisted artificial pile is tufted into a base fabric at a predetermined row pitch and gauge using a tufting machine to form a semi-finished artificial turf product; 3) a bottom adhesive application step of applying an adhesive to the bottom surface of the artificial turf semi-finished product and curing it in an oven to obtain the artificial turf.
Citation Information
Patent Citations
Antibacterial artificial lawn
JP2016069792A
Stretchable laminate having beam-shaped elastic body and molded nonwoven fabric layer
JP2021526062A